Moderation by weight status of the associations between positive and negative weight commentary and body image-related indicators in young adults - Erin K. O’Loughlin; Maryam Marashi; Catherine M. Sabiston; Kristen M. Lucibello; Marie-Pierre Sylvestre; Jennifer L. O’Loughlin (PLoS ONE, 2025)
Objectives To assess whether associations between positive or negative weight commentary and body-related emotions, internalized weight bias, and weight worry differ by weight status among young adult males and females. Methods Participants were from the Nicotine Dependence in Teens study, initiated in 1999–2000. For this cross-sectional analysis, self-report data collected online in 2023 were available for 687 young adults (57% female; Mean age = 35.3 years). Sex-stratified analyses compared mean scores for eight body image-related indicators by frequent positive or negative weight commentary (yes/no) and weight status (lower weight vs. higher weight). Moderation was tested using product terms in multivariable linear regression. Results Among females, 44% reported frequent positive commentary (47% lower weight; 41% higher weight) and 13% reported frequent negative commentary (10% lower weight; 16% higher weight). Positive commentary was associated with lower shame, guilt, embarrassment, and internalized weight bias, with stronger protective effects among females with higher weight. Negative commentary was associated with greater body-related distress and weight-related worry, also with stronger effects among females with higher weight. Among males, positive and negative commentary showed modest associations with body image–related indicators, and there was little evidence that weight status modified these associations. Conclusions Associations between weight commentary and body image-related indicators were moderated by weight status in females but not in males. For women with higher weight, positive remarks were somewhat protective, while negative remarks appeared to have disproportionately adverse effects. Findings suggest the need for weight-neutral, sensitive approaches to weight discussions in clinical and social settings.